Investigating Interactive Learning's Effects on Guard Duty Course Learning Outcomes for Cadet Students - Syam, Makmur; Fauzon, Irfan (Journal of Education Method and Learning Strategy, 2023)
The learning results of cadet students taking the guard duty course are examined in this study to determine the effectiveness of interactive learning. Results of post-test data analysis using a sample of 46 students and the pre-experiment approach revealed a significant improvement in learning outcome scores. The median score grew from 80.3 to 82.5, while the mean score went from 80.5 on the pretest to 83.3 on the posttest. Also noticeably rising were the minimum and maximum scores. This research suggests that interactive learning enhances students' comprehension and knowledge. The constructivism learning theory, which emphasizes the value of active involvement in learning, is in accord with the ideas of this advancement. However, it is also essential to consider other elements like the caliber and drive of the instructors. The findings of this study offer a framework for creating more interactive and participatory learning processes in educational situations.